Desecuritization of migration in Greece: re-visiting “flexicuritization” - Dimari, Georgia; Tzagkarakis, Stylianos Ioannis; Papadakis, Nikos; Citkowska-Kimla, Anna (Frontiers in Political Science, 2025)
IntroductionMigration has emerged as a defining global issue of the 21st century, reshaping political discourse, national policies, and international frameworks. Greece, due to its geographical position, has played a central role in Europe’s migration landscape, particularly during the 2015 refugee crisis.MethodsThis paper explores Greece’s migration governance through the lens of flexicuritization, a concept that integrates state security imperatives with human security concerns. Building on Dimari’s initial formulation, the study extends the theoretical scope of flexicuritization by incorporating political culture and national identity as critical variables influencing securitization practices. Through a case study of Lesvos, the paper empirically investigates the interplay between elite political discourse (2011-2019) and local perceptions of migration, based on 120 securitizing speech acts and 75 semi-structured interviews with market actors.ResultsThe analysis reveals how cultural narratives of identity and otherness inform both public sentiment and policy responses, often legitimizing restrictive migration measures.DiscussionBy grounding the flexicuritization framework in the Greek context, the study proposes a culturally sensitive approach to migration governance that balances security concerns with humanitarian obligations, offering broader implications for frontline states managing similar migratory pressures.